The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1037/a0036943
|View full text |Cite
|
Sign up to set email alerts
|

Same spaces, different races: What can cafeteria seating patterns tell us about intergroup relations in middle school?

Abstract: Using 2 segregation indices--an exposure index previously used in cafeteria studies and an entropy index used for the first time, to our knowledge, in this study--we examined racial segregation in seating patterns among ethnically diverse middle school students in their school cafeteria over a 2-week period. Given the representation of groups in the cafeteria each day, results indicated the expected amount of contact between Asian and White students, but more limited contact between Asian and Latino students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 35 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…We adapted the methods of microanalysis (e.g., Clack, Dixon, & Tredoux, ) to study seating patterns in the cafeteria of one ethnically diverse middle school (Echols, Solomon, & Graham, ). The ethnic composition of the school was 39% Latino, 22% White, 19% Asian, 9% Filipino, 5% African America, and 6% other.…”
Section: Observing Diversity In the Everyday Life Spaces Of Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…We adapted the methods of microanalysis (e.g., Clack, Dixon, & Tredoux, ) to study seating patterns in the cafeteria of one ethnically diverse middle school (Echols, Solomon, & Graham, ). The ethnic composition of the school was 39% Latino, 22% White, 19% Asian, 9% Filipino, 5% African America, and 6% other.…”
Section: Observing Diversity In the Everyday Life Spaces Of Youthmentioning
confidence: 99%
“…We recorded these seating patterns at 15‐min intervals for a 45‐min lunch period. From these data, we calculated an exposure index, which tells us whether voluntary contact between members of different ethnic groups exceeded chance, and an entropy index, which tells us the proportion of the cafeteria population that would need to be reseated to achieve perfect integration (see Echols et al., , for details). Except for Asians and Whites, we found that the dyadic exposure between most of the ethnic groups was less than what would be expected by chance.…”
Section: Observing Diversity In the Everyday Life Spaces Of Youthmentioning
confidence: 99%
“…The USA is the country that comes next in number of studies (N = 5). Here the microecology of segregation has been studied in educational settings: notably, classrooms and other informal settings in university campuses (Cowan, 2005), classrooms and other school settings in an elementary school (Henze, 2001), middle school cafeterias (Echols, Solomon, & Graham, 2014), university dining halls (Lewis, 2012), and youth sports events in the suburbs (Messner & Bozada-Deas, 2009). In Northern Ireland (n = 3), too, studies have explored the meeting halls and buses of segregated schools (McKeown, Cairns, Stringer, & Era, 2012), university lecture theatres (Orr, McKeown, Cairns, & Stringer, 2012), and classrooms of integrated secondary schools (McKeown, Stringer, & Cairns, 2016).…”
Section: Research On the Micro-ecology Of Segregation: A Quantitativementioning
confidence: 99%
“…The club's within-ethnicity heterogeneity is seen as a unique opportunity to gather connections to enhance individuals' own social capital. Echols et al (2014)…”
Section: Authorsmentioning
confidence: 99%
“…Diverse classrooms increase the opportunity for intergroup friendships to form (Moody, ; Turner, Tam, Hewstone, Kenworthy, & Cairns, ), but more than physical proximity is necessary to promote positive intergroup contact and cross‐race friendships (Turner & Cameron, ; Wessel, ). For example, research examining intergroup behaviour in diverse settings has demonstrated that children and young people do not spontaneously engage in intergroup contact with diverse peers (e.g., Echols, Solomon, & Graham, ; McCauley, Plummer, Moskalenko, & Mordkoff, ; McKeown, Stringer, & Cairns, ). Thus, whereas diverse classrooms can offer the exciting opportunity to promote positive intergroup interactions (Hewstone, ), aspects of the school environment may support or hinder students engagement in positive intergroup interactions (Thijs & Verkuyten, ).…”
Section: Promoting Intergroup Contact In Educationmentioning
confidence: 99%